THE IMPORTANCE OF ELECTRONIC VILLAGE BUDGETING INNOVATION TO IMPROVE PUBLIC SERVICES - Nirta Vera Yustanti; Melly Susanti; Sulisti Afriani (Kusuma Negara Business School, 2020)
This study aims to determine the importance of innovation in e-budgeting applications in providing services to the community as well as how to manage local finance effectively and efficiently so that there is transparency in the management of village funds. The method used is a literature review and research results show that the application of e-budgeting in the management of regional finances is very helpful in creating good and clean government. Electronic budgeting is an online innovation that can provide effective and transparent services. In this paper, we discuss how to manage innovation in a company by using theories from existing literature. This discussion includes an innovation framework, the impact of innovation in human services, the advantages and disadvantages of e-village budgeting. The results of this study are e-village budgeting innovation in government in providing services to the public is a new innovation that has advantages and still has weaknesses, therefore there is a need for improvement in electronic village budgeting innovation services.